2022
DOI: 10.1186/s12870-022-03647-0
|View full text |Cite
|
Sign up to set email alerts
|

Sand supplementation favors tropical seagrass Thalassia hemprichii in eutrophic bay: implications for seagrass restoration and management

Abstract: Background Sediment is crucial for the unique marine angiosperm seagrass growth and successful restoration. Sediment modification induced by eutrophication also exacerbates seagrass decline and reduces plantation and transplantation survival rates. However, we lack information regarding the influence of sediment on seagrass photosynthesis and the metabolics, especially regarding the key secondary metabolic flavone. Meanwhile, sulfation of flavonoids in seagrass may mitigate sulfide intrusion, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 79 publications
1
2
0
Order By: Relevance
“…This condition predicted due to substrate in the LMB02 that consist of sandy and mud. This is in accordance with Hans (1996) who stated that Thalassia hemprichii lives better on a slightly sandy muddy substrate, then Jiang et al ( 2017) and Jiang et al (2022) explained that Thalassia hemprichii grows better on coarse sand substrate or in the coral substrate. Besides Thalassia hemprichii, Enhalus acoroides also lives quite well on this type of substrate.…”
Section: Species In All Stationssupporting
confidence: 89%
“…This condition predicted due to substrate in the LMB02 that consist of sandy and mud. This is in accordance with Hans (1996) who stated that Thalassia hemprichii lives better on a slightly sandy muddy substrate, then Jiang et al ( 2017) and Jiang et al (2022) explained that Thalassia hemprichii grows better on coarse sand substrate or in the coral substrate. Besides Thalassia hemprichii, Enhalus acoroides also lives quite well on this type of substrate.…”
Section: Species In All Stationssupporting
confidence: 89%
“…She found that E. acoroides seed settlement and seedling establishment can readily occur at sites with fine sand substrate and lower wave exposure. Another recent study by Jiang et al (2022) also reported sediment's importance on seagrass's growth and survival. According to Jiang et al (2022), seagrass Thalassia hemprichii often grows better on coarse sand substrates because coarse beach sand indirectly enhances photosynthesis in T. hemprichii by reducing sulfide intrusion with lower amino acid and flavonoid concentrations.…”
Section: Resultsmentioning
confidence: 87%
“…Marine seagrasses are a rich source for secondary metabolites, mainly, phenolic compounds [ 11 ]. Thalassia hemperchii is a widespread species of seagrass in the genus Thalassia that is indigenous to the shore of the Red Sea [ 12 ].…”
Section: Introductionmentioning
confidence: 99%